Development of Android-Based Digital Local Tourism Management System (DLTMS): Tourism Marketing Strategy in Dompu Regency - Yeye Suhaety; Nurul Hayat (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to develop a mobile-based Digital Local Tourism Management System (DLTMS) platform as a means to introduce and make it easier for tourists to find tourist destinations in Dompu Regency. The application with the name Pasaka displays several natural, cultural, and culinary attractions, namely: Lakey Beach, Satonda Island, Pacoa Jara, Rimpu Festival, Cera Labu, and other tourist destinations in Dompu Regency. This application has interesting features such as a description of cultural tourist attractions, culinary tourism, regional superior products, and regional cultural events throughout the year. This research uses a Research and Development (R&D) approach. Research and Development (R&D) is research used to produce a specific product. The researcher focuses on an application as well as a guide to Android-based tourism objects that every user will use. The results of the image display on this application are clear and not broken and complete with the caption of the written image. This application is very useful for tourists who want to visit. Therefore, the Pasaka application can help make it easier for them to find out the location of tourist attractions and a marketing strategy to promote tourism destinations in Dompu Regency.